O conceito de cidadania no ensino de Sociologia no estado de São Paulo - Silva, Ricardo Pereira da (2016)
This research sought to answer which is the conception of citizenship resulting from teaching Sociology in the 3rd year of high school, offered by the state of São Paulo, more specifically, at Sorocaba. The desideratum was to verify if the teaching material used for the Sociology class exposes the citizenship as a formal concept, so defined by the liberal sociologist T.H. Marshall. He assumes that there are antagonistic social classes and that the struggle for democratic rights occurs naturally as part of the historical development. Among the authors we use as a reference, the following stand out: besides Marshall, John Locke, Norberto Bobbio, Decio Saes, Newton Duarte, Ivo Tonet, Nilda Teves Ferreira, Marcos Francisco Martins, and others. The literature review worked with the concept of citizenship from the etymology, the perspective of historical and dialectical materialism, from the liberal interpretation of the concept, as well as criticizing the liberal concept. The study also presents a brief historical of sociology teaching in high school and analyze show the concept of citizenship is treated in textbooks, indicated by National Textbook Program. In the last chapter of this work, we presents the results of fieldwork, which consisted in a questionnaire with open and closed questions made to five teachers of Sociology from Sorocaba area and twentyseven students as well.